Global patterns of taxonomic and phylogenetic endemism in liverwort assemblages - Hong Qian; Shenhua Qian (Plant Diversity)
Exploring the worldwide patterns of endemism and the processes that lead to the formation of high-endemism centers is crucial in biogeography. This study examines the geographic distribution and ecological influences on the endemism of liverworts across 390 regions worldwide. We assess phylogenetic endemism and relative phylogenetic endemism in relation to eleven environmental factors, which represent current and Quaternary climate variations, as well as topographic and environmental heterogeneity. Areas with higher endemism in liverworts tend to have higher temperatures, precipitation, and environmental heterogeneity, but lower temperature seasonality and lesser impacts from Quaternary climate changes. Regions exhibiting notably high endemism are predominantly found in tropical Asia, Madagascar, eastern Australia, and the Andes, while those with notably low endemism are generally in temperate Eurasia and North America, parts of Africa, and eastern South America. Centers of neo-endemism are mainly in southern Africa, whereas centers of paleo-endemism are in southern South America, tropical Asia, and New Zealand. Environment variability is a more significant predictor of phylogenetic endemism than current climate conditions, which are themselves more predictive than variables related to Quaternary climate changes. Nevertheless, these three types of explanatory variables combined explain only about one-third of the variance in phylogenetic endemism.